SENTENCE PATTERN USED IN CALUM SCOTT’S SONG LYRICH - Nenojata, Yohanes J; Sama, Gratiana; Kara, Yuliana M D K (Lantern: Journal of Language and Literature, 2023)
Sentence patterns and sentence types are an inseparable unit where each type of sentence contains several sentence patterns. In general, some researchers analyzed sentence patterns in a short story, speech text, news text and others. But in this study will analyze sentence patterns and sentence types in two song lyrics by Calum Scott. Usually in a song lyrics consists of phrases, clauses, and sentences, but the study will analyze how many sentences are there. This study aims to find sentence patterns and sentence types in the two song lyrics. This study uses a qualitative method. The results of the study show that there are six sentence patterns and six types of sentences found in the two songs. No Matter What's first song with details as follows; pattern I (S+VT+DO), pattern II (S+int.V), pattern, pattern IV (S+intr.V+SP), pattern V (S+com.V+DO+OP), and pattern IV (S+pre.V+PC). The second song is Dancing on My Own with the following details; pattern I (S+VT+DO), pattern II (S+int.V), pattern III (S+dist.V+DO+IO), pattern IV (S+intr.V+SP), pattern V (S+com.V+DO+OP), and pattern VI (S+pre.V+PC). While the types of sentences from the two songs, No Matter What and Dancing on My Own there are four types. They are simple sentence, compound sentence, complex sentence, and compound complex sentence.